A 3D Hybrid of Chemically Coupled Nickel Sulfide and Hollow Carbon Spheres for High Performance Lithium–Sulfur Batteries. (17th July 2017) - Ye, Chao; Zhang, Lei; Guo, Chunxian; Li, Dongdong; Vasileff, Anthony; Wang, Haihui; Qiao, Shi‐Zhang
Abstract : Lithium–sulfur batteries are a promising next‐generation energy storage device owing to their high theoretical capacity and the low cost and abundance of sulfur. However, the low conductivity and loss of active sulfur material during operation greatly limit the rating capabilities and cycling stability of lithium–sulfur batteries. In this work, a unique sulfur host hybrid material comprising nanosized nickel sulfide (NiS) uniformly distributed on 3D carbon hollow spheres (C‐HS) is fabricated using an in situ thermal reduction and sulfidation method. In the hybrid material, the nanosized NiS provides a high adsorption capability for polysulfides and the C‐HS serves as a physical confinement for polysulfides and also a 3D electron transfer pathway. Moreover, NiS has strong chemical coupling with the C‐HS, favoring fast charge transfer and redox kinetics of the sulfur electrode. With a sulfur loading of up to 2.3 mg cm −2, the hybrid material‐based lithium–sulfur batteries offer a capacity decay as low as 0.013% per cycle and a capacity of 695 mA h g −1 at 0.5 C after 300 cycles. This unique 3D hybrid material with strong chemical coupling provides a promising sulfur host for high performance lithium–sulfur batteries. Abstract : A unique 3D hybrid of nickel sulfide (NiS) and carbon hollow spheres (C‐HSs) is synthesized as a sulfur host. The uniformly distributed NiS greatly promote adsorption capability toward polysulfides.The C‐HSs increase sulfur loading as well as the overall conductivity. This sulfur host achieves a capacity of 695 mA h g −1 after 300 cycles at 0.5 C.